PENGARUH RASA PERCAYA DIRI DAN PERAN GURU TERHADAP PARTISIPASI BELAJAR IPS SISWA KELAS VIII UPTD SMPN 7 PEMATANGSIANTAR TAHUN AJARAN 2025/2026 - Tia Artika Muliani Manurung; Anton Luvi Siahaan; Debbi Petra Meyana Sitorus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the impact of self-confidence and the teacher's role on social studies participation among eighth-grade students at UPTD SMP Negeri 7 Pematangsiantar (2025/2026). Using a quantitative approach, a sample of 144 students was selected via the Slovin formula. Data were collected through validated questionnaires and analyzed using multiple linear regression, t-tests, and F-tests. Results indicate that self-confidence significantly influences participation tcount 6.870 > ttable 1.977; sig. 0.000). Similarly, the teacher's role exhibits a positive, significant effect. Simultaneously, both variables significantly impact student engagement Fcount 179.088 > Ftable 3.06; sig. 0.000). These findings suggest that higher student self-confidence combined with an optimized teacher's role leads to increased participation in social studies learning. This research underscores the importance of psychological and pedagogical factors in fostering an active classroom environment.